Shared Prospective Models of Land Use and Vegetation for the Mexico-Guatemala Transboundary Area - Nuñez Hernández, Juan Manuel (2022)
The shared border between Mexico and Guatemala is a complex region to analyze due to the diverse dynamics between both countries. One threat to the area is the land-use change, where many drivers of change and environmental conditions make it a priority to analyze. This research studies the land-use changes that occurred between 1990 and 2010; these are used as a basis for constructing a trend scenario to the year 2030 through the use of the multilayer perceptron neural network. The resulting scenario shows the growth of agriculture and urban areas, as well as the loss of forests, other vegetation, and water bodies. This information highlights the need to analyze the socio-environmental implications that this could bring about.